Reduced coenzyme Q10 crystal and preparation

By controlling manufacturing conditions and adding auxiliary ingredients, high-melting-point Form II type reduced coenzyme Q10 crystals were prepared, solving the problem of insufficient oxidative stability and realizing highly oxidatively stable reduced coenzyme Q10 crystals and formulations suitable for various supplement forms.

CN120835873APending Publication Date: 2025-10-24KANEKA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202480019999.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2024-03-27
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

The existing reduced coenzyme Q10 crystals have insufficient oxidative stability in formulations, and are easily oxidized during processing and storage, which affects their application.

Method used

By controlling the manufacturing conditions of reduced coenzyme Q10 crystals, especially the cooling rate and temperature changes during the cooling crystallization process, Form II crystals with a melting point above 53.0℃ were prepared. Appropriate auxiliary components such as lubricants and base materials were added to the formulation to improve oxidative stability.

Benefits of technology

The oxidation rate was lower than 0.35% when stored at 40°C and 75% RH for one month, ensuring the high oxidative stability of reduced coenzyme Q10 crystals and preparations, making them suitable for various supplement forms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120835873A_ABST
    Figure CN120835873A_ABST
Patent Text Reader

Abstract

Provided is a reduced coenzyme Q10 crystal having excellent oxidation stability. The reduced coenzyme Q10 crystal has a maximum melting point of 53.0 DEG C or more when measured at a temperature increase rate of 1 DEG C / min by differential scanning calorimetry (DSC).
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to reduced coenzyme Q10 useful as a raw material for supplements, and particularly to its crystallization and formulation. BACKGROUND

[0002] Coenzyme Q is an essential component widely distributed in organisms from bacteria to mammals, and is well known as a component of the electron transport chain of mitochondria in cells in organisms. For humans, coenzyme Q having a side chain of 10 repeating structures, coenzyme Q10, is the main component, and in organisms, it is usually present in the form of a reduced form at around 40 to 90%.

[0003] With respect to coenzyme Q10, a wide range of physiological activities such as activation of energy production by mitochondrial activation, activation of cardiac function, stabilizing effect on cell membranes, and protective effect on cells by antioxidation are reported, and it is being utilized as a pharmaceutical, a raw material for supplements.

[0004] In the past, coenzyme Q10 used in supplements and the like has been mostly oxidized coenzyme Q10, but since reduced coenzyme Q10 has higher oral absorbability than oxidized coenzyme Q10 (Patent Literature 1), the use of reduced coenzyme Q10 is becoming widespread.

[0005] On the other hand, reduced coenzyme Q10 is easily oxidized by oxygen in the air, and as a supplement having reduced coenzyme Q10 as the main component, a method of filling an oil containing reduced coenzyme Q10 into a soft capsule such as a gelatin capsule is mainly employed.

[0006] When applied to tablets, hard capsules, and the like, it is necessary to improve the oxidation stability of reduced coenzyme Q10, and various studies are being conducted. For example, in Patent Literature 2, it is reported that stabilization is achieved by coating a solid composition containing reduced coenzyme Q10 with a coating medium such as shellac, gelatin, and gum arabic.

[0007] In addition, in recent years, it has been confirmed that there are crystal polymorphs in reduced coenzyme Q10 crystals, and a crystal (Form II crystal) having superior oxidation stability to a conventional crystal (Form I crystal) has been found (Patent Literature 3).

[0008] PRIOR ART DOCUMENTS

[0009] PATENT LITERATURE

[0010] Patent Literature 1: International Publication No. 98 / 07417

[0011] Patent Literature 2: International Publication No. 2008 / 129980

[0012] Patent Literature 3: International Publication No. 2012 / 176842 SUMMARY

[0013] PROBLEMS TO BE SOLVED BY THE INVENTION

[0014] The present inventors, etc. have obtained a preparation which shows a high content of reduced coenzyme Q10 and in which oxidation during processing is inhibited when attempting to produce a tablet-type supplement using Form II crystals of reduced coenzyme Q10, and on the other hand, have confirmed that it is desirable to further improve the oxidation stability if the circulation / storage of the preparation is considered.

[0015] In view of the above, the object of the present invention is to provide a reduced coenzyme Q10 crystal and a preparation which have excellent oxidation stability.

[0016] MEANS FOR SOLVING THE PROBLEMS

[0017] The present inventors, etc. have conducted intensive research, and as a result, have found that in reduced coenzyme Q10 crystals which are referred to as Form II crystals, the melting point fluctuates depending on the manufacturing conditions, etc., and the higher the melting point of the crystals, the higher the oxidation stability exhibited by the crystals, and thus have completed each of the modes of the present invention shown below.

[0018] [1] A crystal which is a reduced coenzyme Q10 crystal, wherein

[0019] The highest melting point when measured at a temperature increase rate of 1°C / min is 53.0°C or higher by differential scanning calorimetry (DSC).

[0020] [2] The crystal according to the above [1], which has an oxidation rate of 0.35 or lower when stored at 40°C, 75% RH for 1 month, as represented by the following formula.

[0021] [3] The crystal according to the above [1] or [2], which shows characteristic peaks at diffraction angles (2θ ± 0.2°) of 11.5°, 18.2°, 19.3°, 22.3°, 23.0°, 33.3° in powder X-ray (Cu-Kα) diffraction.

[0022] [4] A preparation which is a solid preparation containing a crystal of reduced coenzyme Q10, wherein

[0023] The highest melting point (y) (°C) when 30 ± 1 mg of the preparation is measured at a temperature increase rate of 1°C / min by differential scanning calorimetry (DSC) and the amount (x) (mg) of the reduced coenzyme Q10 crystal contained in 30 ± 1 mg of the preparation satisfy the following formula (1),

[0024] (1): y ≥ 0.1441x + 51.737

[0025] This specification includes the disclosure of Japanese Patent Application No. 2023-056001, on which priority of the present application is based.

[0026] Effects of the Invention

[0027] According to the present application, it is possible to provide a reduced coenzyme Q10 crystal and a preparation, which are excellent in oxidation stability and can be applied to supplements in various forms. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 is a graph showing the relationship between the melting point of the reduced coenzyme Q10 crystal and the oxidation rate. ) indicates the relationship between the melting point of the reduced coenzyme Q10 crystal and the oxidation rate. DETAILED DESCRIPTION

[0029] Hereinafter, the present application will be described in detail.

[0030] As described above, there are two crystal polymorphs of Form I and Form II in reduced coenzyme Q10. Specifically, a crystal form of reduced coenzyme Q10 having a melting point of around 48°C and showing characteristic peaks at diffraction angles (2θ ± 0.2°) of 3.1°, 18.7°, 19.0°, 20.2°, 23.0° in powder X-ray (Cu-Kα) diffraction is referred to as Form I crystal, and a crystal form of reduced coenzyme Q10 having a melting point of around 52°C and showing characteristic peaks at diffraction angles (2θ ± 0.2°) of 11.5°, 18.2°, 19.3°, 22.3°, 23.0°, 33.3° in powder X-ray (Cu-Kα) diffraction is referred to as Form II crystal.

[0031] The present inventors and others have conducted research, and as a result, it has been confirmed that, for the crystal referred to as Form II crystal, depending on the manufacturing conditions and the like, the melting point will fluctuate within a certain range, and that the higher the melting point of the crystal, the higher the tendency of the oxidation stability.

[0032] Specifically, it has been confirmed that, by differential scanning calorimetry (DSC), when measured at a temperature increase rate of 1°C / min, a crystal having a highest melting point of 53.0°C or higher shows a significant improvement in oxidation stability compared to a crystal having a melting point lower than the above temperature, and the oxidation rate represented by the following formula reaches 0.35 or less when stored for 1 month in an environment of 40°C, 75% RH. Note that, in the present disclosure, the melting point of the crystal refers to the melting point when measured in differential scanning calorimetry (DSC) with a sample amount of 8 ± 1 mg.

[0033] Oxidation rate (% / day) = (100 - relative QH ratio after storage) / number of days of storage

[0034] Here, "QH ratio" means the ratio of reduced coenzyme Q10 to the total amount of coenzyme Q10 present in the crystal, and is the value calculated from the following formula.

[0035] QH ratio (%) = content of reduced coenzyme Q10 / (content of oxidized coenzyme Q10 + content of reduced coenzyme Q10)

[0036] "Relative QH ratio after storage" means the value obtained by setting the QH ratio before storage to 100 and relativizing the QH ratio after storage, based on the respective QH ratios measured before and after storage. Specifically, it is calculated by the following formula.

[0037] Relative QH ratio after storage (%) = QH ratio after storage / QH ratio before storage x 100

[0038] As for the melting point of the crystal of the present application, as described above, the highest melting point when measured at a temperature increase rate of 1°C / min is 53.0°C or higher, more preferably 53.1°C or higher, 53.2°C or higher, 53.3°C or higher, 53.4°C or higher.

[0039] The upper limit of the melting point of the crystal of the present application is not particularly limited as long as it can be handled / stored as a solid without hindrance, and the highest melting point when measured at a temperature increase rate of 1°C / min is, for example, 55.0°C or lower, preferably 54.5°C or lower, more preferably 54.0°C or lower, further preferably 53.5°C or lower.

[0040] The oxidation rate of the crystal of the present application when stored at 40°C, 75% RH for 1 month is, as described above, 0.35 or lower, more preferably 0.30 or lower, 0.28 or lower, 0.26 or lower, 0.24 or lower, 0.23 or lower.

[0041] As long as it is a reduced coenzyme Q10 crystal and a crystal showing the above-mentioned melting point and / or oxidation rate, it belongs to the crystal of the present application, but it is preferably a crystal showing an XRD diffraction pattern characteristic of Form II crystal. That is, the crystal of the present application is preferably a crystal showing characteristic peaks at diffraction angles (2θ ± 0.2°) 11.5°, 18.2°, 19.3°, 22.3°, 23.0°, 33.3° in powder X-ray (Cu-Kα) diffraction.

[0042] The crystal of the present application can be efficiently obtained by, for example, adding an operation to temporarily increase the temperature in the crystallization tank to dissolve a part of the precipitated crystal in the crystallization process (cooling crystallization method) of reduced coenzyme Q10 Form II crystal.

[0043] The crystallization of Coenzyme Q10 Form II can be performed by, for example, adding pre-obtained Form II crystals as seeds to an ethanol solution containing reduced Coenzyme Q10 and cooling. In terms of cooling, if the cooling rate is too fast, there is a risk of mixing Form I crystals, and therefore the cooling rate is preferably controlled appropriately.

[0044] Specific conditions can be applied to the conditions disclosed in International Publication No. 2022 / 202215, for example, an ethanol solution containing reduced Coenzyme Q10 is brought to 37°C, and seeds are added, after which the cooling rate is controlled to be 45 FTU / min or less in terms of the formazin turbidity (FTU / min) in the crystallization tank in the interval from 1000 FTU to 10000 FTU, whereby high-quality Form II crystals in which Form I crystals are inhibited from being mixed can be obtained. Note that the turbidity change rate is also referred to as the turbidity change speed.

[0045] As one method for obtaining the crystals of the present application, an operation of dissolving part of the precipitated crystals is added to the above-described crystallization process. Specifically, at a certain time point after the turbidity in the crystallization tank, i.e., after the precipitation of crystals can be confirmed, the temperature in the crystallization tank is increased to dissolve part of the precipitated crystals. The "dissolution of part of the crystals" can be detected by a decrease in turbidity (but not to 0). After dissolving part of the crystals, the temperature in the crystallization tank is lowered again, and cooling crystallization is performed again.

[0046] The time point at which the temperature increase is started is not particularly limited as long as there are precipitated crystals in the crystallization tank, but from the viewpoint of avoiding the complete dissolution of the precipitated crystals due to the temperature increase, it is desirable that there be a certain amount of crystals, and in the case where the partial dissolution is confirmed by turbidity change, it is desirable to be within the measurement range of the turbidimeter (below the upper limit of measurement). In general, if turbidity is used as an index, it is preferable to be within the interval from 8000 to 10000 FTU, and in terms of the temperature in the tank, it is preferable to be within the interval from 33 to 37°C.

[0047] The degree of temperature increase is not particularly limited as long as the precipitated crystals are not completely dissolved, and if turbidity change is used as an index, it is desirable that the turbidity decrease be within the interval from 350 to 8000 FTU without becoming zero, and if the temperature in the tank is used as an index, it is preferable that the temperature increase be within the interval from 0.5 to 6.5°C.

[0048] Note that this temperature increase (partial dissolution of precipitated crystals) operation is usually performed once, but it can be performed two or more times as needed.

[0049] The reduced coenzyme Q10 crystal eluted through the above procedure is subjected to solid-liquid separation treatment by filtration or centrifugal separation, and then dried, to be isolated / recovered as the crystal of the present application, in the same manner as the conventional reduced coenzyme Q10 crystal. As the method and conditions for the solid-liquid separation and drying, known conditions can be applied as the method for the solid-liquid separation and drying of the reduced coenzyme Q10 crystal.

[0050] Next, the preparation of the present application will be described. One embodiment of the preparation of the present application is a solid preparation containing the reduced coenzyme Q10 crystal, which satisfies the following equation (1) when the highest melting point (y) (°C) is measured by differential scanning calorimetry (DSC) at a temperature increase rate of 1°C / min for the preparation of 30 ± 1 mg and the amount (x) (mg) of the reduced coenzyme Q10 crystal contained in the preparation of 30 ± 1 mg.

[0051] (1): y ≥ 0.1441x + 51.737

[0052] According to the research by the present inventors, it has been further found through repeated experiments that the preparation containing the reduced coenzyme Q10 crystal has a tendency that the melting point of the reduced coenzyme Q10 crystal observed by DSC decreases compared to the case where the reduced coenzyme Q10 crystal is alone, and the preparation satisfying the above equation (1) has excellent oxidation stability of the reduced coenzyme Q10, and thus can be applied to various forms of supplements and the like. The preparation satisfying the above equation (1) can be obtained, for example, by using the reduced coenzyme Q10 crystal of the present application as the reduced coenzyme Q10 crystal. That is, as another embodiment of the preparation of the present application, a solid preparation containing the reduced coenzyme Q10 crystal of the present application can be cited.

[0053] The above highest melting point (y) (°C) of the preparation is not particularly limited, and is, for example, 51.5°C or higher, more preferably 51.6°C or higher, 51.7°C or higher, 51.8°C or higher, 51.9°C or higher. In addition, the above highest melting point (y) (°C) of the preparation is, for example, 54.0°C or lower, preferably 53.5°C or lower, more preferably 53.0°C or lower, further preferably 52.5°C or lower.

[0054] In addition, when the XRD diffractogram of the preparation is observed, the reduced coenzyme Q10 crystal in the preparation preferably exhibits the characteristic pattern of Form II crystal. That is, the reduced coenzyme Q10 crystal in the preparation preferably shows characteristic peaks at diffraction angles (2θ ± 0.2°) of 11.5°, 18.2°, 19.3°, 22.3°, 23.0°, 33.3° in powder X-ray (Cu-Kα) diffraction.

[0055] The formulation of the present application contains components other than the reduced coenzyme Q10 crystal, and the components other than the reduced coenzyme Q10 crystal are not particularly limited, and can be appropriately selected depending on the use of the formulation, etc. Also, the method for producing the formulation of the present application is not particularly limited, and can be produced using a publicly known method depending on the use of the formulation, etc.

[0056] As the components other than the reduced coenzyme Q10 crystal, lubricants, substrates, etc. can be given.

[0057] As the lubricants, magnesium stearate, calcium stearate, sucrose fatty acid ester, etc. can be given. As the substrates, microcrystalline cellulose, crystalline cellulose, maltitol, starch, HPC (hydroxypropyl cellulose), palatinose, etc. can be given.

[0058] The amount of the reduced coenzyme Q10 crystal contained in the formulation is not particularly limited, and can be appropriately selected depending on the use, etc. within a range not hindering the processing of the formulation. The amount of the reduced coenzyme Q10 crystal contained in the formulation is usually 1 wt% or more, preferably 2 wt% or more, 5 wt% or more, 10 wt% or more. The amount of the reduced coenzyme Q10 crystal contained in the formulation is usually 30 wt% or less, preferably 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less.

[0059] Example

[0060] Hereinafter, the present embodiment will be described with examples, but the present application is not limited by these examples. Also, in the examples, reduced coenzyme Q10 is denoted as QH.

[0061] (Comparative Example 1) Crystals obtained by general cooling crystallization (without temperature elevation in the middle)

[0062] To a 36°C solution (QH reaction liquid) in which 10 wt% of QH was dissolved in ethanol having a purity of 99.5 wt% or more, 2 wt% of Form II QH crystals with respect to the weight of the dissolved QH, which was prepared in advance, was added as a seed crystal, and the precipitation rate of the crystals was controlled at a turbidity change rate of 15.8 FTU / min until 10,000 FTU was reached. After 10,000 FTU was reached, cooling control was performed at 1°C / hr until 25°C, and cooling control was performed at 10°C / hr until 1°C. The QH crystals in the obtained reaction liquid were obtained by pressure filtration, and then vacuum dried for 24 hours to produce dried QH crystals.

[0063] The obtained crystals were subjected to DSC analysis under the conditions shown below, and the melting point was measured, and as a result, the highest melting point temperature was 52.6°C (the highest melting point temperature was taken as the apex of the endothermic peak).

[0064] (DSC measurement conditions)

[0065] Apparatus: DSC200 (Hitachi High-Tech)

[0066] Sample container: aluminum pan & lid (GCA-0052)

[0067] Temperature increase rate: 1°C / min

[0068] Sample amount: 8 ± 1 mg

[0069] Sample particle size: 53 ~ 74 μm

[0070] (Comparative Example 2) Crystallization by general cooling crystallization (without temperature increase in the middle)

[0071] To the QH reaction solution at 37°C, 8 wt% of seed crystal with respect to the weight of dissolved QH was added, and otherwise, QH crystallization was prepared in the same manner as Comparative Example 1.

[0072] The DSC melting point of the obtained QH crystallization was measured under the same conditions as Comparative Example 1, and as a result, the highest melting point temperature was 52.8°C.

[0073] (Comparative Example 2) Crystallization by general cooling crystallization (without temperature increase in the middle)

[0074] At the time point when the reaction solution (QH reaction solution) in which 10 wt% of QH was dissolved in ethanol having a purity of 99.5 wt% or more was 37°C, 8 wt% of Form II QH crystallization with respect to the weight of dissolved QH was added as seed crystal, and the crystallization precipitation rate was controlled at a turbidity change rate of 15.8 FTU / min until 10000 FTU was reached. After 10000 FTU was reached, the temperature was increased to 38.5°C, and after confirming the decrease in turbidity, the crystallization precipitation was performed again at a rate of 25 FTU / min based on the turbidity value until 10000 FTU was reached. After 10000 FTU was reached, cooling was performed at 1°C / hr until 25°C, and cooling was performed at 10°C / hr until 1°C. QH crystallization in the obtained reaction solution was obtained by reduced pressure filtration, and then vacuum dried for 24 hours, and dried QH crystallization was prepared.

[0075] The DSC melting point of the obtained QH crystallization was measured under the same conditions as Comparative Example 1, and as a result, the highest melting point temperature was 53.1°C.

[0076] (Comparative Example 2) Crystallization by general cooling crystallization (without temperature increase in the middle)

[0077] After confirming the temperature increase and the decrease in turbidity, the crystallization rate at which the turbidity reached 10,000 FTU again was set to 15 FTU / min, and QH crystals were produced in the same manner as in Example 1 except for this.

[0078] The DSC melting point of the obtained QH crystals was measured under the same conditions as in Comparative Example 1, and the result showed that the highest melting point temperature was 53.4°C.

[0079] (Example 3) Crystals obtained by crystallization with intermediate temperature increase

[0080] After confirming the temperature increase and the decrease in turbidity, the crystallization rate at which the turbidity reached 10,000 FTU again was set to 15 FTU / min, and QH crystals were produced in the same manner as in Example 1 except for this.

[0081] The DSC melting point of the obtained QH crystals was measured under the same conditions as in Comparative Example 1, and the result showed that the highest melting point temperature was 53.4°C.

[0082] (Example 4, Comparative Example 3)

[0083] The QH crystals produced in Examples 1 to 3 and Comparative Examples 1 and 2 were stored in a thermostat at 40°C and 75% RH for about one month. The reduced coenzyme Q10 content and the oxidized coenzyme Q10 content in the crystals were measured by HPLC (high performance liquid chromatography) before and after the storage, and the QH ratio, the relative QH ratio after the storage, and the oxidation rate described below were calculated from the measurement results.

[0084] (HPLC conditions)

[0085] Column: AS12S05-1546WT (YMC) 150 mm (length) x 4.6 mm (inner diameter)

[0086] Mobile phase: C2H3N:CH3OH = 1:9 (v:v)

[0087] Detection wavelength: 290 nm

[0088] Flow rate: 1 ml / min

[0089] The "QH ratio" refers to the proportion of reduced coenzyme Q10 present in the crystals relative to the total amount of coenzyme Q10, and is calculated by the following formula.

[0090] QH ratio (%) = reduced coenzyme Q10 content / (oxidized coenzyme Q10 content + reduced coenzyme Q10 content)

[0091] "Relative QH ratio after storage" is a value calculated by the following equation, based on respective QH ratios measured before the start of storage and after storage, taking the QH ratio before storage as 100, and relative-izing the QH ratio after storage.

[0092] Relative QH ratio after storage (%) = QH ratio after storage / QH ratio before start of storage x 100

[0093] "Oxidation rate" is a value obtained by dividing the change (decrease) in relative QH ratio during storage by the number of days of storage, and is calculated by the following equation.

[0094] Oxidation rate (% / day) = (100 - relative QH ratio after storage) / number of days of storage

[0095] The results of the measurement of the crystals prepared in each of the examples and comparative examples are summarized in Table 1 below. In addition, a fitting line of the melting point versus the oxidation rate made from the results of Table 1 is shown in Figure 1 .

[0096]

[0097] From Table 1 and Figure 1 it is known that the crystal having a melting point of 53.0°C or higher in Form II has particularly excellent oxidation stability.

[0098] (Example 5)

[0099] The QH crystal (having a highest melting point temperature of 53.1°C) obtained in Example 1 was mixed with magnesium stearate and microcrystalline cellulose in the proportions shown in Table 2 below, to obtain a powder-like preparation.

[0100] The obtained preparation was subjected to DSC analysis under the conditions shown below, and the melting point was measured, and the highest melting point temperature (taking the apex of the endothermic peak as the highest melting point temperature) was calculated. The highest melting point is shown in Table 2 below.

[0101] (DSC measurement conditions)

[0102] Apparatus: DSC200 (Hitachi High-Tech)

[0103] Sample container: aluminum pan & lid (CVB-0008)

[0104] Temperature increase rate: 1°C / min

[0105] Sample amount: 30 ± 1 mg

[0106] Measurement temperature: 35°C to 60°C

[0107]

[0108] (Example 6)

[0109] QH crystals (having a maximum melting point temperature of 53.1°C) 5 mg obtained in Example 1, magnesium stearate 2 mg, and various substrates shown in Table 3 below were mixed to obtain a powder-like preparation (containing 5 wt% of QH powder). Note that HPC in Table 3 means hydroxypropyl cellulose.

[0110] The obtained preparation was subjected to DSC analysis under the conditions shown below, and the melting point was measured, and the maximum melting point temperature (the apex of the endothermic peak was taken as the maximum melting point temperature) was calculated. The maximum melting point is shown in Table 3 below.

[0111] (DSC measurement conditions)

[0112] Apparatus: DSC200 (Hitachi High-Tech)

[0113] Sample container: aluminum pan & lid (CVB-0008)

[0114] Temperature increase rate: 1°C / min

[0115] Sample amount: 30 ± 1 mg

[0116] Measurement temperature: 35°C to 60°C

[0117]

[0118] The upper limit value and / or the lower limit value of the numerical range described in the present specification can be combined arbitrarily to define a preferable range. For example, the upper limit value and the lower limit value of the numerical range can be combined arbitrarily to define a preferable range, the upper limit values of the numerical range can be combined arbitrarily with each other to define a preferable range, and the lower limit values of the numerical range can be combined arbitrarily with each other to define a preferable range.

[0119] Throughout the present specification, the singular form is intended to include the concept of the plural form unless specifically stated otherwise. Therefore, the singular form of the article (for example, "a", "an", "the", and the like when English) is intended to include the concept of the plural form unless specifically stated otherwise.

[0120] All publications, patents, and patent applications cited in the present specification are hereby incorporated by reference in their entirety.

Claims

1. A crystal which is a reduced coenzyme Q10 crystal, wherein The highest melting point is 53.0°C or higher when measured at a temperature increase rate of 1°C / min by differential scanning calorimetry (DSC).

2. The crystal according to claim 1, which has an oxidation rate of 0.35 or lower when stored at 40°C, 75% RH for 1 month, the oxidation rate being represented by the following formula, Oxidation rate (% / day) = (100 - relative QH ratio after storage) / number of days of storage.

3. The crystal according to claim 1 or 2, which shows characteristic peaks at diffraction angles (2Θ ± 0.2°) 11.5°, 18.2°, 19.3°, 22.3°, 23.0°, 33.3° in powder X-ray (Cu-Kα) diffraction.

4. A preparation which is a solid preparation containing a crystal of reduced coenzyme Q10, wherein The highest melting point (y) (°C) when 30 ± 1 mg of the preparation is measured at a temperature increase rate of 1°C / min by differential scanning calorimetry (DSC) and the amount (x) (mg) of the reduced coenzyme Q10 crystal contained in 30 ± 1 mg of the preparation satisfy the following formula (1), (1): y > 0.1441x + 51.737.

Citation Information

Patent Citations

  • TGF-B-receptor ectodomain fusion molecules and uses thereof

    JP2023056001A

  • Pharmaceutical composition comprising coenzyme Q10

    WO1998007417A1

  • Particulate composition comprising reduced coenzyme q10, and method for production thereof

    WO2008129980A1

  • Reduced coenzyme q10 crystal having excellent stability

    WO2012176842A1

  • Method for producing form-ii type reduced coenzyme q10 crystal or crystalline solid of same, and crystallizing apparatus

    WO2022202215A1